2022
DOI: 10.1002/fes3.362
|View full text |Cite
|
Sign up to set email alerts
|

Crop improvements for future‐proofing European food systems: A focus‐group‐driven analysis of agricultural production stakeholder priorities and viewpoints

Abstract: Crop breeding is one of the main tools which can assist in future‐proofing food systems for more sustainable outcomes. In order to ensure priorities are aligned with the needs and wants of food system actors, it is essential to engage with key stakeholders to understand preferences on plant breeding solutions. This study presents results from a series of online focus groups conducted with agricultural production related stakeholders (i.e. farmers and farmer representatives, policymakers and NGOs) regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Focussing on sustainability in communication activities might increase the opportunity to agree on shared values among different stakeholders and could provide a starting point to broaden the debate on applications of plant genome editing. Two recently conducted citizen juries 1 with consumer experts and societal stakeholders concluded that the acceptance of new plant breeding techniques by society could be increased when its application serves goals with a societal dimension such as environmental sustainability, resilience and quality (Nair et al, 2022, Stetkiewicz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Focussing on sustainability in communication activities might increase the opportunity to agree on shared values among different stakeholders and could provide a starting point to broaden the debate on applications of plant genome editing. Two recently conducted citizen juries 1 with consumer experts and societal stakeholders concluded that the acceptance of new plant breeding techniques by society could be increased when its application serves goals with a societal dimension such as environmental sustainability, resilience and quality (Nair et al, 2022, Stetkiewicz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The CropBooster-P database can be considered as a literature repository that can be continuously updated with state-or-the-art literature in the fields of yield, nutritional quality and sustainability. Within the project, the database serves as a foundation because it is both scientifically sound overview of the current state of the art in distinct research fields, as well as a resource with which to engage in discussion with stakeholder groups (Nair et al, 2022;Stetkiewicz et al, 2022) and the general public in later phases of the CropBooster-P project.…”
Section: Figurementioning
confidence: 99%
“…To this end, WP3 ('Engage society') engages the general public in a dialog about the need for crop improvement. To do so, consumers and other non-expert lay people are engaged in a series of workshops and events (Nair et al, 2022;Stetkiewicz et al, 2022) to find out how the issues of the CropBooster-P project are perceived and what the specific objectives of different societal groups are. To understand and advise how to best communicate complex scientific information to different societal groups, including the general public in Europe, attitudes, expectations and appropriate means of communication are explored through questionnaires and interviews in WP6 ('Outreach and communication').…”
Section: Towards the Cropbooster-p Roadmapmentioning
confidence: 99%
See 2 more Smart Citations